2022
DOI: 10.1177/14604086221104934
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and psychosocial aspects of major trauma care in the United Kingdom: A scoping review of primary research

Abstract: Introduction More people are surviving major trauma, often with life changing injuries. Alongside physical injury, many survivors of major trauma experience psychological and psychosocial impacts. Presently, there is little guidance at the UK national level for psychological and psychosocial aspects of major trauma care. Set in the context of the regional model of major trauma care implemented in the UK in 2012, the purpose of this review was to identify and bring together primary research about psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Qualitative studies focusing on patient perspectives of recovery following isolated SCI or TBI were also excluded as these patients tend to have a vastly different clinical care pathway and recovery trajectory. 20…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative studies focusing on patient perspectives of recovery following isolated SCI or TBI were also excluded as these patients tend to have a vastly different clinical care pathway and recovery trajectory. 20…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] However, little is known about longer-term functional outcomes or how patients experience recovery, limiting our ability to develop the best pathways or services for patients and evaluate the effectiveness of rehabilitation interventions. [11][12][13] Primary research studies have started to investigate the long-term psychosocial impacts of major trauma, [8][9][10] and previous studies have identified persistent pain, poor rates of return to work, and psychological manifestations such as anxiety as indicators of poor recovery. [14][15][16][17] However, patient's lived experience of traumatic injury remains unquantified and poorly understood by rehabilitation specialists and researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although major trauma policy documents across the UK and Ireland (ibid) incorporate psychological and psychosocial aspects of care, the level of detail across them varies. There is evidence that these aspects of major trauma care are often underserved in the UK 23 . Although major trauma networks may operate differently, the aim of this research was to gain insight into current provision and operationalisation of psychological and psychosocial aspects of major trauma care for survivors and their families across the UK and Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that these aspects of major trauma care are often underserved in the UK. 23 Although major trauma networks may operate differently, the aim of this research was to gain insight into the current provision and operationalisation of psychological and psychosocial aspects of major trauma care for survivors and their families across the UK and Ireland.…”
Section: Introductionmentioning
confidence: 99%